Validity of clinical examination in screening pediatric minor head trauma with loss of consciousness - Jayapal, Karthick; Mansour, Hassan Adnan (International Journal of Contemporary Pediatrics, 2018)
Background: Minor head injury is the most common presentation in the emergency room for pediatric cases. Though most of them present with intact consciousness, there is an increased risk of primary and secondary brain damage, owing to several mechanical and cellular pathophysiological changes following trauma. Computed Tomography (CT) is the gold standard diagnostic tool for trauma; however, it has been reported that 30% of CT examinations are unwarranted. This study was carried out to evaluate the diagnostic validity of clinical examination in pediatric minor head trauma. Methods: This cross-sectional study was carried out among 355 patients between 1-15 years of age presenting to the ER, who had closed minor head trauma and loss of consciousness. Patients with GCS of 13-15 were included. A thorough clinical examination including head and neck was carried out. All the participants were subjected to CT examination. Data was entered and analyzed using Microsoft Excel spreadsheet. Results: The prevalence of minor head trauma detected by CT examination was 21.4%. The sensitivity and specificity of clinical examination were 71% and 63.8% respectively. The negative predictive value of the screening test was 89%. Conclusions: The value of clinical examination in detecting minor head trauma may be well complemented by the development of standardized clinical criteria which may be evaluated for its diagnostic capability. Following efficient clinical tool will minimize CT examinations and thereby prevent lethal complications due to radiation overdose in the pediatric population.